Urgensi Akta Notaris Dalam Pengalihan Hak Atas Merek Melalui Hibah Sebagai Bentuk Kepastian Hukum - Anggun Mulia, Yen Yen; Elly Hernawati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
Trademark rights can be transferred in several ways, namely inheritance, gift, will, agreement and other reasons permitted by law. The transfer of rights to a trademark through a gift requires a deed and this is stipulated in article 1682 of the Civil Code which reads as follows: "no gift is made without a notarial deed" the gift is included in the form of a gratuitous agreement, meaning is a unilateral agreement made by the donor while he is still alive to provide an item free of charge to the recipient of the gift. A notary is a public official who has the authority to make authentic deeds which have physical, formal and material evidentiary power and can be used as perfect evidence if a legal problem arises in the future. Keyword: Transfer of trademark rights; Grand deed; Notary.